Biotinidase Deficiency and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Authors from La Jolla, USA and Florence, Italy report the case of a boy who was first admitted to hospital at 5 years of age because of acute somnolence, alopecia, keratoconjunctivitis and perioral stomatitis associated with lactic acidaemia.